A study on the prospects of vacuum gamma irradiation to enhance crosslinking for 3D-Printing PLA/MCC biocomposite filaments - Rashed Almasri; Yoko Akiyama; Yuichiro Manabe; Fuminobu Sato (Physics Open, 2023)
3D-printing or Additive Manufacturing (AM) has been growing as a rapid manufacturing process for many different applications, with Poly (Lactic Acid) as one of the most used materials for 3D-printing. PLA shows great promise for many applications to achieve the goals of the SDGs due to its biodegradability and biocompatibility but lacks when it comes to mechanical strength and thermal resistance. In this study, microcrystalline cellulose (MCC) fibers were introduced as a reinforcement to PLA. The biocomposite filaments were irradiated in a vacuum to enhance the crosslinking. Gamma-ray irradiation in a vacuum has successfully shown signs of crosslinking by increasing the tensile strength and thermal stability of the biocomposite, indicating an enhancement for PLA/MCC for various applications. On the other hand, changes in thermal properties also indicated that irradiation may reduce the processability of the composite, so it is necessary to study the conditions under which the mechanical properties and processability are compatible.